The role of agricultural productivity in economic growth in middle-income countries: An empirical investigation - Arif Eser Güzel; Cemil Serhat Akin (Economic Journal of Emerging Markets, 2021)
Purpose - This study investigates the role of agricultural productivity in economic growth in middle-income countries.Methods - This study utilizes the data of 53 middle-income countries over the period 1991-2017 and provides robust estimations using second-generation panel data methods considering cross-sectional dependency.Findings - The estimation results of the Common Correlated Effects Mean Group (CCEMG), Dynamic-CCEMG, and biased-corrected form of Dynamic-CCEMG, suggest that agricultural productivity is the main engine of economic growth. Additional findings show that economic growth is positively associated with both physical capital and human capital. This paper does not find any significant relationship between trade openness and economic growth.Implications - This study reveals that the industrialization process in middle-income countries to boost economic growth can be accelerated by implementing policies to increase productivity in the agricultural sector.Originality - This study focuses on analyzing the effect of agricultural productivity neglected mainly in recent studies on economic growth. This paper develops a second-generation estimator that considers cross-sectional dependence.